Mammalian Cochlear Hair Cell Regeneration and Ribbon Synapse Reformation - Xiaoling Lu; Yilai Shu; Mingliang Tang; Huawei Li (Neural Plasticity)
Hair cells (HCs) are the sensory preceptor cells in the inner ear, which play an important role in hearing and balance. The HCs of organ of Corti are susceptible to noise, ototoxic drugs, and infections, thus resulting in permanent hearing loss. Recent approaches of HCs regeneration provide new directions for finding the treatment of sensor neural deafness. To have normal hearing function, the regenerated HCs must be reinnervated by nerve fibers and reform ribbon synapse with the dendrite of spiral ganglion neuron through nerve regeneration. In this review, we discuss the research progress in HC regeneration, the synaptic plasticity, and the reinnervation of new regenerated HCs in mammalian inner ear.